Children's experiences of agency when learning English in the classroom of a collectivist culture. (June 2021) - Hargreaves, Eleanore; Elhawary, Dalia
Abstract: This paper explores agency in a collectivist culture to investigate whether, and if so how, school-children experience agency as supportive to learning to speak English in the classroom of a collectivist culture. It draws on Ryan and Deci's (2019) Self-Determination Theory (SDT) to examine nine primary classrooms in three schools in Alexandria, Arab Republic of Egypt. The research involved 281 primary-school-children who completed open-ended sentences about experiences in the ELT classroom, observations of the nine participating classes and 18 individual interviews. Our findings provided support for the universality of the need for autonomy (reflecting agency) in learning to speak English within a collectivist culture, in that the sample children expressed the need for greater autonomy. They also the inter-relatedness of the three basic needs of SDT, competence, autonomy and relatedness. Our findings suggest that children were encouraged by their schooling system to develop Control or Impersonal Orientations rather than Autonomy Orientations. These were sustained through children's fear of making mistakes and teachers scolding them which inhibited their sense of agency and capacity for speaking in English. Some children found that agency was less inhibited when they did simultaneous pairwork, if their needs for competence and relatedness were also satisfied.